Navigating AI-Driven Workplaces: Human Resource Practices Shaping Generation Z Employees’ Work Experiences - Mella Mardayanti; Dian Priatiningsih (ICON Publisher, 2026)
The increasing adoption of artificial intelligence in human resource management has transformed how work is organized and experienced, particularly among Generation Z employees. This study examines how human resource practices shape employee work experiences in AI-driven workplaces. Drawing on a sensemaking perspective, the study adopts an interpretive qualitative approach to explore how Generation Z employees perceive and interpret HR practices mediated by algorithmic systems. Data were collected through in-depth interviews with employees working in digitally intensive organizations that utilize AI-supported HR processes. The findings reveal that AI-driven workplaces do not generate uniform employee experiences. Instead, work experiences are shaped by HR practices that influence perceptions of transparency, fairness, and organizational support. HR practices that emphasize communication, feedback, and ethical considerations facilitate constructive sensemaking and positive emotional responses. Conversely, limited HR engagement amplifies uncertainty, anxiety, and concerns regarding algorithmic control. The study contributes to digital HRM literature by highlighting the central role of HR practices as interpretive mechanisms in AI-driven contexts. Practically, the findings suggest that organizations must adopt human-centered HR approaches to ensure sustainable and responsible use of artificial intelligence at work.